Analysis of Making A Vlog to Minimize Public Speak Anxiety Among EFL Students - Andewi, Widi; Waziana, Winia (IALLTEACH (Issues In Applied Linguistics & Language Teaching), 2023)
Anxiety is the most dominant of psychological problem that faced by students in learning speaking. This study focused on analysis of making a vlog to minimize public speaks anxiety among EFL students. This study answer the following question, â€œHow does video blog minimize public speak anxiety among EFL students?â€ Descriptive qualitative method as simply observing a behavior was used in this study. Frist-semester students of Institut Bakti nusantara were the participants of this study which consist of 10 students, majoring in Information system. There were two ways for collecting data, namely: observations and inteview. They were assigned to make a video of speaking performance on a topic â€œAdvertisementâ€. The result could be concluded that making video blog is useful to minimize public speak anxiety among EFL student. Besides that, a vlog is considered as one of useful stategy which can provide students motivation for being confidence in public speaking. Futhermore, creating a vlog can give enjoyable and attractive learning atmosphere and students will feel more comfortable, relaxed, and motivated to practice their speaking skill. Even though a vlog has been proven to reduce anxiety levels, there are several things that must be considered when using a vlog as a media for learning speaking. Lecturers are expected to be more creative and innovative in order to make students become more interested in speaking English. Lectures always know studentsâ€™ speaking anxiety level and studentsâ€™ condition in learning speaking due to not all of students have the same characteristics to be able to accept all types of media.